Report of the Work of the National Joint Committee for Spanish Relief, The British Committee for Refugees from Spain and The Basque Children's Committee (1939)
1939 038-0069-006 Since the outbreak of the War in Spain on 18th July, 1936, voluntary organisations throughout the world have raised more than £4,500,000 for Spanish Relief. Great Britain tops the list, just ahead of America and France, with a total voluntary subscription of over one million pounds. The National Joint Committee for Spanish Relief and its affiliated committees have raised nearly half a million pounds for the prosecution of the various relief plans. In the peak period, which ran from November, 1938 to June, 1939, the amount raised by the National Joint Committee alone reached the remarkable total of £115,000. Throughout the whole period of its activities, the National Joint Committee for Spanish Relief and its associated committees have enjoyed the financial and moral support of every section of the British public in response to an appeal based on the strongest humanitarian grounds. The result has been an achievement practically unparalleled in the history of voluntary relief movements in this country. What has been done with the money raised ? And what remains to be done ? The following pages will show. 292/946/38/69(VI)